THE USE OF KNOW WANT TO LEARN (KWL) METHOD IN IMPROVING STUDENT’S LEVEL OF READING COMPREHENSION IN SENIOR HIGH SCHOOL - Musliha, Rina; Jabu, Baso; Munir, Munir (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The purpose of this research was to determine the use of the KWL method in improving students' level of reading comprehension in senior high school. This research uses quantitative methods in pre-experimental classes as a research strategy. The respondents of this research were 10th-grade students of SMAN 11 Makassar in the odd semester of the 2022/2023 academic year. Respondents were selected randomly to analyze the use of the KWL method in improving students' reading comprehension levels. The instrument of this research is Pre-test, Treatment, and Post-test. Outcomes of data analysis found, that there was an effect of using the KWL method in improving the level of students' reading comprehension and students' responses to the use of the KWL method in learning reading comprehension through Pre-test, treatment, and Post-test were seen to increase. The average score of the students' Pre-test was in the "poor" category, while after the treatment, an average score for the Post-test was categorized as "good". The Post-test mean score after treatment is higher than the Pre-test mean.